2021
DOI: 10.3390/ijms22073693
|View full text |Cite
|
Sign up to set email alerts
|

Marine Collagen Hydrolysates Promote Collagen Synthesis, Viability and Proliferation While Downregulating the Synthesis of Pro-Catabolic Markers in Human Articular Chondrocytes

Abstract: Cartilage is a non-innervated and non-vascularized tissue. It is composed of one main cell type, the chondrocyte, which governs homeostasis within the cartilage tissue, but has low metabolic activity. Articular cartilage undergoes substantial stresses that lead to chondral defects, and inevitably osteoarthritis (OA) due to the low intrinsic repair capacity of cartilage. OA remains an incurable degenerative disease. In this context, several dietary supplements have shown promising results, notably in the relief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Previous research has shown that low‐molecular‐weight collagen peptide or fish collagen peptide is a potential candidate for the treatment of OA that stimulates cartilage regeneration using a rabbit anterior cruciate ligament transection (ACLT) model of induced OA and chondrocytes isolated from a patient with OA (Lee et al, 2021 ; Ohnishi et al, 2013 ). Fish collagen hydrolysates were also shown to enhance collagen production, viability, and proliferation in human articular chondrocytes (Bourdon et al, 2021 ). In addition, OVX mice or rats have previously been used in the study of osteoporosis following menopause (Lemini et al, 2015 ; Strom et al, 2012 ; Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that low‐molecular‐weight collagen peptide or fish collagen peptide is a potential candidate for the treatment of OA that stimulates cartilage regeneration using a rabbit anterior cruciate ligament transection (ACLT) model of induced OA and chondrocytes isolated from a patient with OA (Lee et al, 2021 ; Ohnishi et al, 2013 ). Fish collagen hydrolysates were also shown to enhance collagen production, viability, and proliferation in human articular chondrocytes (Bourdon et al, 2021 ). In addition, OVX mice or rats have previously been used in the study of osteoporosis following menopause (Lemini et al, 2015 ; Strom et al, 2012 ; Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marine collagen hydrolysate has recently been reported as a novel natural antioxidant in biomedical applications as an alternative to conventional mammalian (such as bovine and porcine sources) collagen hydrolysates [38]. Aquatic collagen sources have many advantages over land animals, such as weak immunogenicity, biocompatibility, no religious and moral conflicts, and low chances of causing transmissible diseases.…”
Section: Species As Collagen Sourcesmentioning
confidence: 99%